Validación del recurso solar en el Ecuador para aplicaciones de media y alta temperatura - Arla Odio, Sandra (2017)
The study provides real information on the solar energy resource through global radiation measurements carried out at meteorological stations located along the heavy oil pipeline route at 15 points of interest in the provinces Nueva Loja, Napo, Pichincha and Esmeraldas, The average of these is compared with the average values obtained through globally used procedures: satellite observations, software estimates and estimates by mathematical models. This study makes available to the designers of solar energy systems in Ecuador reliable data of the global solar radiation, so that the systems with real data can be dimensioned and also the degree of error is known when using these procedures; Revealing the differences found between the mean values of radiation determined by simulation and correlation models with those measured on the surface.